Investigating English Students’ Motivation in Speaking Class during New Normal Era - Feny Martina; Ali Akbarjono; Heny Friantary; Tri Nengsi Puspita Sari (Journal of English Education and Teaching, 2021)
Motivation is one of the most important factors and greatly influences the learning process. The purpose of this study was to determine how the level of motivation of students in the speaking class during the new nomal era, namely the second semester students of the English Department of IAIN Bengkulu. This study used a descriptive quantitative approach. The techniques used in collecting data were questionnaire and interview. The questionnaire consists of 36 questions divided into intrinsic and extrinsic motivation. The data are presented statistically using percentage, frequency, arithmetic mean, and standard deviation division. The results showed that the mean score of intrinsic motivation (3.89) was higher than the average score of extrinsic motivation (3.39). However, the overall motivation average of 3.68 is considered a high level of motivation despite currently studying in the Covid-19 pandemic conditions. The results of this study indicate that the majority of students learn English in the speaking class because of intrinsic motivation. They actively speak and learn English because of their own inner desires. Based on the findings of this study, several relevant learning implications and useful motivations are recommended to increase student motivation.